Implicit variable-radius arc canal surfaces for solid modeling. Issue 3 (16th April 2017) - Fryazinov, Oleg; Pasko, Alexander
ABSTRACT: In this paper we consider the problem of obtaining an implicit form for the canal surface whose spine is the arc and the radius changes linearly in respect to the angle. We present a number of different solutions to the problem including exact and approximated ones and discuss the scenarios where each of the solutions is appropriate to use in solid modeling with real functions. GRAPHICAL ABSTRACT: